PERSONAL POTENTIAL IN OVERCOMING THE SOCIO- PSYCHOLOGICAL CONSEQUENCES OF WAR AND PANDEMIC - Avanesyan, H.M.; Asriyan, E.V. (Modern Psychology, 2021)
In current situation in Armenia, the problem of personal success and maintaining effective behavior should be considered as an important condition for a healthy society and the formation of a stable state. The aim of the paper is to identify the role of personal potential as a main socio-psychological factor that determine the process of overcoming and coping the current situation in the Republic of Armenia (post-war and the epidemic situation). Our hypothesis is that personal potential1, including psychological capital and its development, can be considered as an indicator of the well-being of society.